Diet and Mobility in Byzantine Western Anatolia: Carbon and Nitrogen Isotopic Ratios and Ancient DNA Evidence from Barcın Höyük and Kadıkalesi Anaia - Ozbal, Rana; Buyukkarakaya, Ali Metin; Uysal, Gulfem; Butun, Erge; Gerritsen, Fokke; Akbaba, Ali; Somel, Mehmet (Cambridge Univ Press, 2026)
This study presents the integrated results of stable carbon (delta 13C) and nitrogen (delta 15N) isotope and aDNA analyses, conducted to examine dietary and mobility practices in two mid- to late Byzantine communities in western Anatolia: the coastal cosmopolitan site of Kad & imath;kalesi Anaia and the rural inland settlement of Barc & imath;n H & ouml;y & uuml;k. Isotopic data from thirty-eight individuals indicate that both populations primarily consumed terrestrial C-3-based resources. At Kad & imath;kalesi, delta 15N values show greater variability, suggesting more differentiated access to animal protein sources, whereas the rural community at Barc & imath;n H & ouml;y & uuml;k exhibits isotopic homogeneity, consistent with more uniform dietary practices and an equitable access to food. Kad & imath;kalesi also shows intra-site dietary variation by age and sex, while Barc & imath;n is again more homogeneous. At Barc & imath;n, aDNA results indicate a predominant local genetic continuity, suggesting a stable population; a single instance of external ancestry is attested by a male individual with affinities to western populations, particularly from eastern Europe, in line with historical military resettlement patterns (stratiotika ktemata). By integrating isotopic and genomic evidence, this study demonstrates how ancestry and mobility shaped dietary habits, offering insights into the interplay of urbanism, mobility, and social organization in the Byzantine period. Cette & eacute;tude pr & eacute;sente les r & eacute;sultats combin & eacute;s d'analyses des isotopes stables du carbone (delta 13C) et de l'azote (delta 15N) et des analyses de l'ADN ancien extraits d'& eacute;chantillons provenant de deux communaut & eacute;s en Anatolie occidentale : le site cosmopolitan de Kad & imath;kalesi Anaia sur la c & ocirc;te ionienne et le site rural de Barc & imath;n H & ouml;y & uuml;k dans l'int & eacute;rieur du pays. Le but & eacute;tait d'examiner les pratiques alimentaires et la mobilit & eacute; attest & eacute;es sur ces deux sites d'& eacute;poque byzantine moyenne & agrave; tardive. Les donn & eacute;es isotopiques provenant de trente-huit individus indiquent que les deux populations consommaient principalement des ressources terrestres de type C3. Les valeurs de l'azote & agrave; Kad & imath;kalesi sont plus variables qu'& agrave; Barc & imath;n, ce qui sugg & egrave;re un acc & egrave;s plus diff & eacute;renci & eacute; aux prot & eacute;ines d'origine animale; la communaut & eacute; rurale de Barc & imath;n r & eacute;v & egrave;le un profil isotopique plus homog & egrave;ne, correspondant & agrave; un r & eacute;gime alimentaire plus uniforme et & agrave; un acc & egrave;s & eacute;quitable aux ressources alimentaires. Une alimentation plus vair & eacute;e selon l'& acirc;ge et le sexe des habitants est attest & eacute;e au sein du site de Kad & imath;kalesi, tandis qu'elle est & agrave; nouveau plus homog & egrave;ne & agrave; Barc & imath;n. Les analyses de l'ADN ancien de Barc & imath;n r & eacute;v & egrave;lent une communaut & eacute; essentiellement locale, ce qui indiquerait une population stable; un seul cas d' ascendance g & eacute;n & eacute;tique externe a & eacute;t & eacute; relev & eacute;; il s'agit d'un individue masculin dont les affinit & eacute;s avec les populations occidentales, en particulier d'Europe orientale, pourraient & ecirc;tre mises en rapport avec la relocalisation de personnel militaire connu historiquement (stratiotika ktemata). L'int & eacute;gration des donn & eacute;es g & eacute;nomiques et isotopiques illustre comment l'ascendance et la mobilit & eacute; des populations influen & ccedil;aient leurs pratiques alimentaires et nous & eacute;claire sur les interactions entre l'urbanisme, la mobilit & eacute; et l'organisation sociale & agrave; l'& eacute;poque byzantine. Translation by Madeleine Hummler Diese Studie enth & auml;lt die kombinierten Ergebnisse von Analysen der stabilen Isotope von Kohlenstoff (delta 13C) und Stickstoff (delta 15N) sowie von aDNA, die aus zwei Gemeinschaften in Westanatolien stammen: die kosmopolitische Stadt Kad & imath;kalesi Anaia an der ionischen K & uuml;ste und die l & auml;ndliche Siedlung Barc & imath;n H & ouml;y & uuml;k im Landesinnern. Ziel war es, die Ern & auml;hrung und die Mobilit & auml;t in diesen mittel- bis sp & auml;tbyzantinischen St & auml;tten zu untersuchen. Die Isotopenanalyse von achtunddrei ss ig Individuen zeigt, dass beide Gemeinschaften haupts & auml;chlich terrestrische Nahrungsmittel von Typus C3 konsumierten. In Kad & imath;kalesi weisen die Sickstoffwerte eine gr & ouml;ss ere Variabilit & auml;t als in Barc & imath;n auf, was auf einen differenzierten Zugang zu tierischen Proteinquellen deutet; hingegen weist die l & auml;ndliche Gemeinschaft in Barc & imath;n ein homogenes Isotopenprofil auf, das mit einer einheitlichen Ern & auml;hrung und einem gleichberechtigten Zugang zu Lebensmitteln & uuml;bereinstimmt. Es gibt auch alters- und geschlechtsspezifische Unterschiede in der Ern & auml;hrung innerhalb Kad & imath;kalesi, w & auml;hrend Barc & imath;n wiederum homogener ist. Die Resultate de aDNA-Analyse von Barc & imath;n weisen auf eine & uuml;berwiegend lokale genetische Zusammensetzung, was auf eine stabile Bev & ouml;lkerung hindeuten sollte. Ein einziger Fall externer Abstammung wurde festgestellt, namentlich ein Individuum m & auml;nnlichen Geschlechts mit genetischen Affinit & auml;ten zu westlichen Bev & ouml;lkerungsgruppen, insbesondere in Osteuropa, was mit der historischen Besiedlung von Milit & auml;rpersonal (stratiotika ktemata) zusammenh & auml;ngen k & ouml;nnte. Die integrierten isotopischen und genomischen Angaben zeigen, wie Abstammung und Mobilit & auml;t die Ern & auml;hrung gepr & auml;gt haben und bietet Einblicke & uuml;ber die Beziehungen zwischen Urbanismus, Mobilit & auml;t und soziale Organisation in byzantinischer Zeit. Translation by Madeleine Hummler
Keywords: Stable Isotope Analysis; Byzantine Anatolia; Deltac-13 And Deltan-15; Adna; Stratiotika Ktemata; Barc & Imath;N H & Ouml;Y & Uuml;K; Kad & Imath;Kalesi Anaia; Analyse Des Isotopes Stables; Anatolie Byzantine; Deltac-13 Et Deltan-15; Adn Ancien; Stabile Isotopenanalyse; Byzantinisches Anatolien